Data from: A local evaluation of the individual state-space to scale up Bayesian spatial capture recapture - Milleret, Cyril; Dupont, Pierre; Bonenfant, Christophe; Brøseth, Henrik; Flagstad, Øystein; Sutherland, Chris; Bischof, Richard (Zenodo, 2018)
1. Spatial capture-recapture models (SCR) are used to estimate animal density and to investigate a range of problems in spatial ecology that cannot be addressed with traditional non-spatial methods. Bayesian approaches in particular offer tremendous flexibility for SCR modelling. Increasingly, SCR data are being collected over very large spatial extents making analysis computational intensive, sometimes prohibitively so. 2. To mitigate the computational burden of large-scale SCR models, we developed an improved formulation of the Bayesian SCR model that uses local evaluation of the individual state-space (LESS). Based on prior knowledge about a species' home range size, we created square evaluation windows that restrict the spatial domain in which an individual's detection probability (detector window) and activity center location (AC window) are estimated. We used simulations and empirical data analyses to assess the performance and bias of SCR with LESS. 3. LESS produced unbiased estimates of SCR parameters when the AC window width was ≥5σ (σ: the scale parameter of the half-normal detection function), and when the detector window extended beyond the edge of the AC window by 2σ. Importantly, LESS considerably decreased the computation time needed for fitting SCR models. In our simulations, LESS increased the computation speed of SCR models up to 57 fold. We demonstrate the power of this new approach by mapping the density of an elusive large carnivore – the wolverine (Gulo gulo) – with an unprecedented resolution and across the species' entire range in Norway (more than 200 000 km2). 4. Our approach helps overcome a major computational obstacle to population and landscape-level SCR analyses. The LESS implementation in a Bayesian framework makes the customization and fitting of SCR accessible for practitioners that are working at scales that are relevant for conservation and management. RData and Rscript for the wolverine example WolverineData.RData is the RData file necessary to perform the analysis of the ...